A systematized review and qualitative synthesis of potential risk factors associated with the occurrence of non‐O157 Shiga toxin‐producing Escherichia coli (STEC) in the primary production of cattle. Issue 3 (20th March 2022) - Withenshaw, Susan M.; Smith, Richard P.; Davies, Rob; Smith, Alice E. O.; Gray, Elizabeth; Rodgers, John
Abstract: Human infection with Shiga toxin‐producing Escherichia coli (STEC) causes an estimated 2.8 million cases of acute illness worldwide each year. Serogroup O157 is the most commonly diagnosed STEC in humans, but cases linked to non‐O157 STEC serogroups have increased recently due to increased surveillance and improvements to detection methods. Cattle are an important reservoir for STEC O157 and the same may be true for non‐O157 STEC; therefore, reducing the occurrence of these pathogens in cattle could mitigate human infection risk. A systematized literature review of articles published within the Scopus database since 2010 (employing a partially systematic approach) was therefore conducted followed by qualitative synthesis of evidence to provide a structured overview of potential risk factors for non‐O157 STEC in primary cattle production. Overall, few relevant studies were identified ( n  = 22), highlighting that more studies are needed. Consistently significant associations were only identified with respect to cattle age (broadly higher rate of isolation from young animals compared to adults) and season of sampling (generally increased isolation of non‐O157 STEC in summer). However, wide variation in study designs, including notable differences in laboratory detection methods, means drawing more general conclusions is currently not possible based on the results of this review. However, it is likely that the development of more sensitive methods for non‐O157 STEC detection in potential livestock reservoirs and increased standardization across statistically sound epidemiological investigations are required to identify pertinent risk factors.